Effects of a Pharmacist-Designed Clinical Decision Support System on Antimicrobial Stewardship - Amor-García, Miguel Ángel; Chamorro-de-Vega, Esther; Rodríguez-González, Carmen Guadalupe; Iglesias-Peinado, Irene; Moreno-Díaz, Raquel (Applied Clinical Informatics, 2024)
Background Clinical decision support systems (CDSSs) are computer applications, which can be applied to give guidance to practitioners in antimicrobial stewardship (AS) activities; however, further information is needed for their optimal use.Objectives Our objective was to analyze the implementation of a CDSS program in a second-level hospital, describing alerts, recommendations, and the effects on consumption and clinical outcomes.Methods In October 2020, a pharmacist-driven CDSS designed for AS was implemented in a second-level hospital. The program provides a list of alerts related to antimicrobial treatment and microbiology, which were automatized for revision by the AS professionals. To analyze the implementation of the CDSS, a pre–post-intervention, retrospective study was designed. AS-triggered alerts and recommendations (total number and rate of acceptance) were compiled. The effect of the CDSS was measured using antimicrobial consumption, duration of antimicrobial treatments, in-hospital mortality, and length of stay (LOS) for patients admitted for infectious causes.Results The AS team revised a total of 7,543 alerts and 772 patients had at least one recommendation, with an acceptance rate of 79.3%. Antimicrobial consumption decreased from 691.1 to 656.8 defined daily doses (DDD)/1,000 beds-month (p = 0.04) and the duration of antimicrobial treatment from 3.6 to 3.3 days (p < 0.01). In-hospital mortality decreased from 6.6 to 6.2% (p = 0.46) and mean LOS from 7.2 to 6.2 days (p < 0.01).Conclusion The implementation of a CDSS resulted in a significant reduction of antimicrobial DDD, duration of antimicrobial treatments, and hospital LOS. There was no significant difference in mortality.
Keywords: clinical decision support system; antimicrobial stewardship; alert; optimization